The Effect of Diasporic Business Networks on International Trade Flows. Issue 2 (15th April 2013) - Sangita, Seema
Abstract International migration flows increase bilateral trade flows between countries through different channels, including creation of diasporic networks that transmit information. These networks have the potential to reduce information barriers and search costs in international trade. This paper quantifies the information effect of diaspora networks, using a panel data set of bilateral migration stocks and bilateral trade data that has been classified into intermediate and final goods. It shows that the migrants' role in exchange of information through business networks does lead to a significant increase in trade among countries. Moreover, the paper finds that this effect is greatest in the case of differentiated goods and that the highly educated migrants are most effective in business networking. Also, this paper addresses the issue of direction of causality between international migration and trade by creating a unique instrumental variable based on citizenship laws of the countries of destination.